The Relationship Between Emotional Intelligence and Mental Health with the Mediating Role of Quality of Life in Patients with Multiple Sclerosis - Ataeii, Behnaz; Sepehri, Shohre; Tanhadoost, Katayoun; Alirezaiee, Vafa; Moraveji, Mahtab (Health Nexus, 2024)
The main objective of the present study was to determine the relationship between emotional intelligence and mental health with the mediating role of the quality of life in patients with multiple sclerosis. The research method was descriptive-correlational with a structural equation modeling approach. The population included all patients with multiple sclerosis in Kashan in the year 2022, from whom 65 patients visiting Shahid Beheshti Hospital in Kashan were selected through convenience sampling and responded to the Goldberg and Hiller Mental Health Questionnaires (1979), Schutte Self-Report Emotional Intelligence (SSREI), and the Hobart et al. Quality of Life Scale for MS Patients (2001). Data were analyzed using SPSS version 22 and AMOS, employing Pearson correlation tests and structural equation modeling. The results showed that the correlation between emotional intelligence and mental health was positive and significant. The correlation between quality of life and mental health was also positive and significant. Furthermore, quality of life played a mediating role in the relationship between emotional intelligence and mental health in patients with MS. Therefore, emotional intelligence and quality of life play an important role in the mental health of patients with MS. In developing therapeutic programs for these patients, factors affecting emotional intelligence and quality of life should be considered.